428. Mobile Phone Access and Comfort: Implications for HIV and Tuberculosis Care in India and South Africa. (26th November 2018) - Cox, Sarah N; Elf, Jessica; Lokhande, Rahul; Ogale, Yasmin P; DiAndreth, Lisa; Dupuis, Elisa; Milovanovic, Minja; Mpongose, Nthabiseng; Martinson, Neil; Mave, Vidya; Suryavanshi, Nishi; Gupta, Amita; et al.
Abstract: Background: India and South Africa shoulder the greatest global burden of TB and HIV, but care retention in these countries is suboptimal. Integration of mHealth into the health system has potential to strengthen retention. We conducted a study in two high burden yet disparate settings, Pune, India and Matlosana, South Africa, to (1) identify factors associated with mobile phone access, comfort of use and (2) understand long-term behavioral patterns of mobile phone access. Methods: We conducted a cross-sectional study to assess demographics, mobile phone access, and comfort of use, followed by a longitudinal study to determine long-term access among adult participants (≥18 years) from 2014 to 2016. Participants were recruited from the TB clinic at Sassoon Government hospital in Pune and from four public clinics serving the general population in Matlosana. Univariate odds ratios compared characteristics of participants with discomfort texting to those who expressed comfort, as well as those unable to be contacted at six months vs. those contacted. We included variables significantly associated at the univariate level ( P < 0.10), and those determined of importance a priori, in a multivariable logistic regression. Results: We enrolled a total of 261 participants; 136 in India, 125 in South Africa. The ability to contact participants steadily decreased from 90% ( n = 122) contacted at week one to 57% ( n = 75) contacted at six months in India and 93% ( n = 116) at week one and 70% ( n = 88) at six months in South Africa (Figure 1). For India, adjusted analysis revealed that texting discomfort was significantly higher in unemployed (OR 4.97, 95% CI: 1.12, 22.09) and 35+ year old (OR 1.10, 95% CI: 1.04, 1.16) participants, while significantly lower in those with higher education (OR 0.04, 95% CI: 0.01, 0.14). In South Africa, 91% of participants ( n = 114) reported comfort with text messaging. Conclusion: The ability to maintain contact with participants by mobile phone in India and South Africa was poor at the 6 month timepoint. While mHealth has the potential to transform HIV and TB care in endemic countries, alternative approaches may be needed for certain subpopulations, including those who are older, unemployed and with lower education. Disclosures: All authors: No reported disclosures.